Optimizing The Role of ZISWAF in Empowering Community Economies: Challenges, Opportunities and Strategies for Increasing Public Awareness - Ash-Shiddiqy, Muhammad; Sobirin, Mohamad; Ahalla Tsauro, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research aims to explore the role of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) as philanthropic instruments in promoting economic empowerment within communities. The study seeks to analyze the level of public awareness regarding the potential of ZISWAF to foster economic growth and improve community welfare. The study adopts a library research approach, synthesizing findings from existing literature related to the definition, concept, and implementation of ZISWAF across different contexts. By reviewing and analyzing these sources, the study evaluates the relationship between public awareness of ZISWAF and its impact on economic empowerment. The findings reveal that public awareness of ZISWAF plays a crucial role in determining the effectiveness of its impact on economic empowerment. A comprehensive understanding of ZISWAF is shown to be vital for its successful implementation. However, the research also highlights several challenges hindering its optimal use such as inadequate education on ZISWAF, regulatory barriers, and insufficient coordination among relevant stakeholders. These obstacles limit the potential of ZISWAF in fully contributing to economic empowerment. The study provides several recommendations for overcoming the challenges identified. It suggests strengthening educational initiatives to increase public knowledge about ZISWAF, encourage cross-sectoral collaboration between different organizations and sectors, and leverage technology to enhance the delivery and impact of ZISWAF initiatives. These measures aim to optimize the role of ZISWAF in supporting community economic empowerment and improving overall welfare. This research offers a significant contribution to the understanding of ZISWAF's potential as a philanthropic tool for economic empowerment. It highlights the importance of public awareness and proposes strategies to enhance the effectiveness of ZISWAF in promoting community welfare. The study’s findings serve as a valuable resource for policymakers, practitioners, and researchers aiming to optimize ZISWAF's impact on economic growth and community development.